The Vatican Apostolic Library and European travellers - Zhumagulov Kalkaman Tursynovich; Sadykova Raikhan Onalbaykyzy; Tursyn Sanzhar (World Scientific Reports, 2025)
Numerous copies and notes by Italian travelers have saved, taken from the Vatican archives in Rome, the Vallicelli, Barberini, and Magliabecca libraries, the churches of Santa Maria sub-Minerva, and the Riccardi Library in Florence. However, the Vatican Apostolic Library deserves special attention. Such research can help reconstruct a complete picture of the foreign relations of Kazakhstan and its predecessors with Europe and other civilizations, which is especially important for reconstructing international relations in different historical eras. Access to rare sources and knowledge facilitates the development of the academic community. The Vatican Apostolic Library (Biblioteca Apostolica Vaticana) was founded by Pope Nicholas in 1451. The Vatican Library ranks first in Europe for the antiquity and richness of its manuscripts, that is, manuscripts and bibliographic rarities. The magnificent Sistine Hall displays some of the rarest exhibits, including an ancient 4th-century Bible manuscript; a 6th-century Gospel of Matthew; a palimpsest, a parchment manuscript containing much of Cicero's De Repubblica; and four copies of Virgil from the 3rd to 5th centuries.